Compartmentalisation of [FeFe]‐hydrogenase maturation in Chlamydomonas reinhardtii. (26th April 2017) - Sawyer, Anne; Bai, Yu; Lu, Yinghua; Hemschemeier, Anja; Happe, Thomas
Summary: Molecular hydrogen (H2 ) can be produced in green microalgae by [FeFe]‐hydrogenases as a direct product of photosynthesis. The Chlamydomonas reinhardtii hydrogenase HYDA1 contains a catalytic site comprising a classic [4Fe4S] cluster linked to a unique 2Fe sub‐cluster. From in vitro studies it appears that the [4Fe4S] cluster is incorporated first by the housekeeping FeS cluster assembly machinery, followed by the 2Fe sub‐cluster, whose biosynthesis requires the specific maturases HYDEF and HYDG. To investigate the maturation process in vivo, we expressed HYDA1 from the C. reinhardtii chloroplast and nuclear genomes (with and without a chloroplast transit peptide) in a hydrogenase‐deficient mutant strain, and examined the cellular enzymatic hydrogenase activity, as well as in vivo H2 production. The transformants expressing HYDA1 from the chloroplast genome displayed levels of H2 production comparable to the wild type, as did the transformants expressing full‐length HYDA1 from the nuclear genome. In contrast, cells equipped with cytoplasm‐targeted HYDA1 produced inactive enzyme, which could only be activated in vitro after reconstitution of the [4Fe4S] cluster. This indicates that the HYDA1 FeS cluster can only be built by the chloroplastic FeS cluster assembly machinery. Further, the expression of a bacterial hydrogenase gene, CPI, from the C. reinhardtii chloroplast genome resulted in H2 ‐producing strains, demonstrating that a hydrogenase with a very different structure can fulfil the role of HYDA1 in vivo and that overexpression of foreign hydrogenases in C. reinhardtii is possible. All chloroplast transformants were stable and no toxic effects were seen from HYDA1 or CPI expression. Significance Statement: The assembly of the Chlamydomonas reinhardtii [FeFe]‐hydrogenase HYDA1 iron sulfur cluster, despite being intensively studied in vitro, is still not understood in the natural host. We found that the HYDA1 iron sulfur cluster can only be assembled in the chloroplast, showing that the C. reinhardtii HYDA1 FeS cluster maturation machinery is not interchangeable.